Teacher Health and Well-Being Paradigm - Lucia ȘCHIOPU (ACROSS)
This article describes the dimensions of teachers’ well-being and the multilevel perspectives of teaching as the levels of institutional design satisfaction, institutional commitment, school climate, school engagement, emotional exhaustion etc. Also, it examines the school context that embraces leadership style, management team, and school communication system that are pivotal in decreasing extreme tiredness and enhancing job contentment. There have been established moderating factors that influence the relationship between the students’ engagement and academic performance.